PENGEMBANGAN MEDIA PEMBELAJARAN SMART BOX TERHADAP MINAT DAN PEMAHAMAN MEMBACA PESERTA DIDIK KELAS V DI SDN SIMANGU - Almahi, Elisyah; Fajari, Ami Milda; Janiati, Nur Indah; Fajrudin, Lili (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to develop a Smart Box learning media for Indonesian language learning, specifically on procedural text material for fifth-grade students at SD Negeri Simangu, in order to improve students’ interest and reading comprehension. The research used a development study with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The trial subjects were fifth-grade students at SD Negeri Simangu. Data were collected through observation, interviews, documentation, validation sheets, questionnaires, and tests. The results of expert validation showed that the media received a score of 97% from media experts, categorized as “very valid,” and 100% from material experts, also categorized as “very valid.” Student response questionnaires during the trial obtained a score of 1878, categorized as “very good.” In conclusion, the Smart Box learning media is considered highly valid, practical, and suitable for use in the learning process.